Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, dan Capital Intensity Terhadap Tax Avoidance - Erika Agustina Nur Anisa; Nursiam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of profitability, leverage, company size, and capital intensity on tax avoidance. This study uses a quantitative method. The type of data in this study is secondary data. The population in this study is property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. The sample used was 157 data with a purposive sampling technique. The analysis technique used in this study is multiple linear regression analysis, classical assumption testing and hypothesis testing. The results of this study indicate that profitability, leverage and company size do not affect tax avoidance. Meanwhile, capital intensity affects tax avoidance.